2009
DOI: 10.1177/104063870902100108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Susceptibility Test Breakpoints Used to Predict mecA-Mediated Resistance in Staphylococcus Pseudintevmedius Isolated from Dogs

Abstract: Abstract. Clinical and Laboratory Standards Institute interpretive breakpoints for in vitro susceptibility tests that predict mecA-mediated oxacillin resistance in Staphylococcus pseudintermedius isolates from animals have been changed twice in the past decade. Moreover, there are no counterpart recommendations for human isolates of S. pseudintermedius. Individual medical and veterinary laboratories variably use interpretive breakpoints identical to those recommended for use with Staphylococcus aureus or ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
105
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 18 publications
(38 reference statements)
8
105
2
Order By: Relevance
“…Furthermore, the findings presented in the current study demonstrate that an unacceptably higher rate of false-negative results occur with application of the 2008 CLSI criteria, consistent with recent work. 2 Therefore, it is advised that veterinary diagnostic laboratories abstain from using the 2008 CLSI criteria when evaluating methicillin resistance in canine S. pseudintermedius. The 2004 CLSI criteria for oxacillin Kirby-Bauer disk diffusion and oxacillin broth microdilution should be used to evaluate methicillin resistance in canine S. pseudintermedius isolates.…”
Section: ) Application Of the 2004 Interpretive Criterion Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the findings presented in the current study demonstrate that an unacceptably higher rate of false-negative results occur with application of the 2008 CLSI criteria, consistent with recent work. 2 Therefore, it is advised that veterinary diagnostic laboratories abstain from using the 2008 CLSI criteria when evaluating methicillin resistance in canine S. pseudintermedius. The 2004 CLSI criteria for oxacillin Kirby-Bauer disk diffusion and oxacillin broth microdilution should be used to evaluate methicillin resistance in canine S. pseudintermedius isolates.…”
Section: ) Application Of the 2004 Interpretive Criterion Ofmentioning
confidence: 99%
“…17,22 Methicillin-resistant S. pseudintermedius (MRSP) has been increasingly reported as a primary pathogen in canine infections. 2,12,13,19,23,24 All methicillin-resistant staphylococci are, by convention, regarded to be resistant to all b-lactam antibiotics in vivo. 5,7 Cephalosporins are the most common antimicrobials used to treat S. pseudintermedius infections in dogs 18 but are not efficacious for the treatment of MRSP infections.…”
mentioning
confidence: 99%
“…The use of oxacillin disk diffusion along with the interpretative criteria applied to Staphylococcus aureus has led to a high percentage of false-negative results thus making it rather inappropriate as a screening tool (Bemis et al, 2009). In 2009, the Clinical and Laboratory Standards Institute (CLSI) of Veterinary Antimicrobial Susceptibility Testing (VAST) subcommittee re-evaluated the interpretative criteria, proposing an oxacillin MIC of ≥0.5 mg/L (agar and broth dilution) and a zone diameter of ≤17 mm (disc diffusion) as highly reliable for the detection of mecA in S. pseudintermedius strains (Papich, 2010).…”
Section: Methicillin-resistant S Pseudinter-medius (Mrsp)mentioning
confidence: 99%
“…For example, in the Netherlands, there was an increase from 0.9% in 2004 to 7% in data published in 2016. [5][6][7][8][9][10][11][12][13] Vanessa Schmidt concluded that MDR strains were common in the population studied. It is increasingly important to obtain bacterial cultures before treatment.…”
mentioning
confidence: 99%